Numerical Study of Early Detection of Tuberculosis Infected with High Sensitivity Plasmonic Sensor - Irawan, Dedi; Azhar; Ramadhan, Khaikal; Marwin, Azwir; Marwan, Arip (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
In this work, a photonic crystal fiber based on a plasmonic sensor for the early detection of tuberculosis has been designed with finite element analysis. The component is constructed with a substrate layer made of fused silica material, which is then coated with a thin film of TiO2 layer as an adhesive layer to strongly attach the Au layer with the silica fiber surface. The TiO2 layer has an optimal thickness of 45 nm, while the Au layer has a thickness of 50 nm. The sensor design has a refractive index (RI) detection range from 1.27 RIU to 1.37 RIU, it also shows a maximum wavelength sensitivity (WS), maximum amplitude sensitivity (AS), sensor resolution (SR), and sensor accuracy (SA) of 20,000 nm/RIU (x-polarized) and 17.000 nm/RIU( y-polarized), -211.38 1/RIU (x-polarized) and -211.211 1/RIU (y-polarized), 9.17 x 10−5 RIU (x-polarized) and 1 x 10−4 RIU (y-polarized), and 0.025/nm respectively. Tuberculosis exhibits a normal and infected RI range of 1.343 RIU to 1.351 RIU. Therefore, the proposed sensor design is capable of detecting four types of TB infections with high sensitivity.